1984
DOI: 10.1021/jm00369a012
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of sparsomycin and its analogs: octylsparsomycin: The first analog more active than sparsomycin

Abstract: Nine analogues of sparsomycin were synthesized, and their cytostatic activity was studied in an in vitro clonogenic L1210 assay by measuring the inhibition of colony formation. The activity of an analogue, expressed as an ID50 value, was compared to that of sparsomycin. Each possesses not more than two structural modifications of the sparsomycin molecule 1. Comparison of the activity of with that of the stereomers, having RCSS, SCSS, and RCRS chirality, respectively, shows that the S configuration of the chira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…the chiral C atom and the S atom of the sulfoxide group (Ottenheijm et al, 1981). A structureactivity relationship study showed that the configuration of the molecule plays an important role in its biological acitivity (Liskamp & Clostee, 1984;Lin & Dubois, 1977). Here, we report the crystal structure of the title compound, (I), which is an analogue of sparsomycin with high antibacterial activity.…”
Section: Commentmentioning
confidence: 94%
“…the chiral C atom and the S atom of the sulfoxide group (Ottenheijm et al, 1981). A structureactivity relationship study showed that the configuration of the molecule plays an important role in its biological acitivity (Liskamp & Clostee, 1984;Lin & Dubois, 1977). Here, we report the crystal structure of the title compound, (I), which is an analogue of sparsomycin with high antibacterial activity.…”
Section: Commentmentioning
confidence: 94%
“…Sparsomycin (3) and its alkyl analogues, ethylsparsomycin (4), n-butylsparsomycin (5), allylsparsomycin (6) and benzylsparsomycin (7), were synthesized from (14a-18a) by following the optimized conditions via MOM-ethers (21)(22)(23)(24)(25) 3) All these new compounds gave satisfactory NMR and IR data together with HRMS. We stored sparoxomycin and its analogues (3)(4)(5)(6)(7) in the dark after their recrystallization from MeOH, because the trans double bond tended to easily isomerize to the cis-isomer in a solution.…”
Section: Synthesis Of Sparsomycin and Its Alkyl Analoguesmentioning
confidence: 99%
“…[7][8][9][10] These potentially important biological activities have made 3 an attractive target for a potential antineoplastic compound. 11) Since thê rst synthetic study of sparsomycin in 1976, 12) synthetic studies of sparsomycin, [13][14][15] total synthesis, [16][17][18] biosynthesis, 19,20) and structure-activity relationship studies [21][22][23][24][25][26][27] have been widely reported. There have been many reports on the antitumor, antibacterial, antifungal, and antiviral properties; however, normalization of the phenotype of oncogene-transformed cells by 3 and its analogues has not previously been reported.…”
mentioning
confidence: 99%
“…24 Compound 4a, especially, is a potential key intermediate for a one pot synthesis of the pyrimidinylacrylate residue of sparsomycin, 25 a metabolite isolated from Streptomyces sparsogenes and Streptomyce cuspidosporus, 26 which shows many kinds of biological activities. [27][28][29][30][31][32] Compounds 3a,b and 4a,b could also work as convenient building blocks for the synthesis of a series of heterocycles and bis-heterocycles.…”
mentioning
confidence: 99%